2004
DOI: 10.1002/mrc.1420
|View full text |Cite
|
Sign up to set email alerts
|

NMR investigations of Co(III) coordination compounds oriented in a dilute lyotropic liquid crystal

Abstract: A swollen lamellar phase, based on sodium dodecyl sulfate, pentanol and NaBr brine, was examined by means of NMR spectroscopy of isotopes with quadrupolar characteristics, namely 2H, 17O, 23Na and 81Br, present at natural abundance. Such a dilute lyotropic liquid crystal was capable of inducing a preferential orientation of the cobalt coordination compounds [Co(en)3]3+ and Co(acac)3, the 59Co NMR signals of which displayed quadrupolar splittings. Moreover, it imparted alignment in the magnetic field to the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…To this day, the large chemical shift of this nucleus, on the order of 20 000 ppm, together with rather favorable NMR properties, make 59 Co NMR spectroscopy a highly sensitive probe for the electronic structure, geometrical parameters, and reactivities of cobalt complexes . In the surge of the blossoming life sciences, interest in 59 Co NMR of Co-containing biomolecules or model complexes thereof has recently been renewed. Since the mid-1990s, the tools of density functional theory (DFT) have successfully been employed to calculate transition-metal chemical shifts, and the 59 Co nucleus has been an early target for such computations. In these studies, which confirmed the suitability of the B3LYP hybrid functional for chemical shift calculations of transition metals, static computations were performed for optimized or experimental geometries. Current developments are directed to go beyond such a static picture in order to account for the dynamic nature of matter, thereby striving for an increase in the accuracy of theoretical NMR parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this day, the large chemical shift of this nucleus, on the order of 20 000 ppm, together with rather favorable NMR properties, make 59 Co NMR spectroscopy a highly sensitive probe for the electronic structure, geometrical parameters, and reactivities of cobalt complexes . In the surge of the blossoming life sciences, interest in 59 Co NMR of Co-containing biomolecules or model complexes thereof has recently been renewed. Since the mid-1990s, the tools of density functional theory (DFT) have successfully been employed to calculate transition-metal chemical shifts, and the 59 Co nucleus has been an early target for such computations. In these studies, which confirmed the suitability of the B3LYP hybrid functional for chemical shift calculations of transition metals, static computations were performed for optimized or experimental geometries. Current developments are directed to go beyond such a static picture in order to account for the dynamic nature of matter, thereby striving for an increase in the accuracy of theoretical NMR parameters.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the surge of the blossoming life sciences, interest in 59 Co NMR of Cocontaining biomolecules or model complexes thereof has recently been renewed. [6][7][8][9] Since the mid-1990s, the tools of density functional theory (DFT) have successfully been employed to calculate transition-metal chemical shifts, [10][11][12][13] and the 59 Co nucleus has been an early target for such computations. [14][15][16][17] In these studies, which confirmed the suitability of the B3LYP hybrid functional for chemical shift calculations of transition metals, 18 static computations were performed for optimized or experimental geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In the former case, the swelling solvent is oil (either n-dodecane [17] or n-heptane) and in the latter brine (a 0.2-M NaBr water solution). [18] Some 23 Na and 2 H NMR measurements were also carried out.…”
Section: S81mentioning
confidence: 99%
“…The samples were prepared by weighing appropriate amounts of SDS and pentanol and either water and hydrocarbon (either n-dodecane, [17] samples d1 and d2, or n-heptane, samples h1 and h2) or brine (NaBr 0.2-M solution, [18] samples b1, b2 and b3) in 10-mm NMR tubes. The relevant compositions are reported in Table 1.…”
Section: Experimental Preparation Of Samplesmentioning
confidence: 99%
“…A swollen lamellar phase based on sodium dodecyl sulfate, pentanol and NaBr brine, has been examined by means of NMR spectroscopy of quadrupolar nuclei, namely 2 H, 17 O, 23 Na and 81 Br, present at natural abundance. 134 This dilute lyotropic liquid crystal was found to be capable of inducing a preferential orientation of the cobalt coordination compounds [Co(en) 3 ] 31 and Co(acac) 3 , and of organocobaloxime [ClCD 2 Co(Hdmg)2H 2 O], which were monitored by the quadrupolar splittings of 59 Co NMR signals in the former case and deuterium in the latter case.…”
Section: Structure and Orientation Of Small Moleculesmentioning
confidence: 99%